The Relationship between Growth-Inequality-Poverty Triangle and Environmental Degradation: Unveiling the Reality - Syeda Anam Hassan; Khalid Zaman; Shah Gul (Arab Economic and Business Journal, 2015)
It is important to recognize that increase in well-being is no longer dependent on further economic growth, but on economic and social well-being, which means that the decline in carbon dioxide emission without reducing real wellbeing and growth. The aim of this study is to investigate the main driving forces affecting short and long-run carbon emissions pattern due to changes in growth, inequality and poverty triangle in Pakistan over the period 1980 - 2011 by using multivariate cointegration approach. This study uses five different models i.e., each model have an important policy implication in the context of Pakistan. The results indicate that, on the short run, there is a significant negative relationship between economic growth & carbon emissions and economic growth & poverty while there is a positive relationship between i) economic growth & income inequality; and ii) poverty & income inequality. On the long-run, there is a significant positive relationship between GDP & income inequality, carbon dioxide emissions & income inequality, and poverty & income inequality in Pakistan. On the other side, there is a negative relationship between carbon emissions & economic growth, carbon emissions & income inequality, and economic growth & income inequality. The results of environmental Kuznets curve (EKC) hypothesis show an inverted U-shaped trajectory in relation to economic growth in Pakistan. This study contributes to the debate on the existence and policy relevance of the EKC for Pakistan. The conclusion ensures the sustainability of an urgent need to look beyond the EKC by adopting courageous policy measures of environmental preservation in Pakistan irrespective of the country's level of income. For reduction of CO2 emission, environmental progressive management policies, economic transport system regulations, and low emit fuel consumption by industries are the need of the world.
Keywords: 330; Economic growth; Income inequality; Poverty; Environment